2010
DOI: 10.1093/humrep/dep465
|View full text |Cite
|
Sign up to set email alerts
|

Sperm DNA: organization, protection and vulnerability: from basic science to clinical applications--a position report

Abstract: This article reports the results of the most recent in a series of EHSRE workshops designed to synthesize the current state of the field in Andrology and provide recommendations for future work (for details see Appendix). Its focus is on methods for detecting sperm DNA damage and potential application of new knowledge about sperm chromatin organization, vulnerability and repair to improve the diagnosis and treatment of clinical infertility associated with that damage. Equally important is the use and reliabili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
181
1
3

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 277 publications
(187 citation statements)
references
References 133 publications
2
181
1
3
Order By: Relevance
“…Among these, the excision repair pathways remove most of the physical damage to DNA as well as replication errors. However, mature spermatozoa being transcrptionally inert is not at par to repair the damage and the high proportion of embryo DNA damage are thought to be derived from male gamete [2]. Also, genetic polymorphisms of DNA repair genes (XRCC1, XPD6, XPD23) were significantly associated with high DFI [35].…”
Section: Discussionmentioning
confidence: 99%
“…Among these, the excision repair pathways remove most of the physical damage to DNA as well as replication errors. However, mature spermatozoa being transcrptionally inert is not at par to repair the damage and the high proportion of embryo DNA damage are thought to be derived from male gamete [2]. Also, genetic polymorphisms of DNA repair genes (XRCC1, XPD6, XPD23) were significantly associated with high DFI [35].…”
Section: Discussionmentioning
confidence: 99%
“…It was shown that there is variation in DAZ copy number in infertile men when using real time PCR [44] and that copy number variation affect total motile sperm count [45]. On the other hand there are reports showing DAZ gene is vulnerable to damage by environmental genotoxic agents such as ionizing radiation [23][24][25][26][27], and spermatozoa are particularly susceptible to ROS-induced damage due to presence of large quantities of polyunsaturated fatty acids and low concentrations of scavenging enzymes in their plasma membranes [46]. Also there are reports showing absence of DAZ genes in spermatozoa of infertile men with somatic DAZ deletions [32].…”
Section: Discussionmentioning
confidence: 99%
“…Perhaps some of the most exciting research in the field is from emerging studies that suggest that the process of spermatogenesis and fertilization is potentially mediated through a variety of other mechanisms that might be associated with infertility phenotypes, including: epigenetic modifications, 84,85 ubiquitination, 86,87 genome organization perturbations, 88 spermatozoal RNAs, 89 proteomics, 90 environmental contaminants and pharmacological agents that may contribute to sperm DNA damage 91 among others.…”
Section: Emerging Research In the Field Of Male Infertilitymentioning
confidence: 99%